2020
DOI: 10.1007/s42452-020-2752-x
|View full text |Cite
|
Sign up to set email alerts
|

Stability research on spinning of ultra-thin-wall aluminum alloy tube

Abstract: In this paper, the instability in spinning process of ultra-thin-wall tube is analyzed, and the influence law of different parameters of roller and main process parameters in spinning forming process. Firstly, the forward spinning finite element model of ultra-thin wall tube is established and its reliability is verified. It is concluded that the instability of ultra-thinwall aluminum alloy tube during spinning is caused by its poor rigidity and material flow disorder. The effects of different parameters of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…For the starting and higher ranges, its effect on cylindricity error is opposite to the middle range. This is further corroborated by the results reported by Wang et al [23] who have studied the spinning stability as a function of the process parameters. It has been found that the increase in the feed rate causes a decrease in the equivalent plastic strain and it is predicted that a larger or smaller feed rate than the optimum one will result in excessive diameter expansion.…”
Section: Resultssupporting
confidence: 87%
“…For the starting and higher ranges, its effect on cylindricity error is opposite to the middle range. This is further corroborated by the results reported by Wang et al [23] who have studied the spinning stability as a function of the process parameters. It has been found that the increase in the feed rate causes a decrease in the equivalent plastic strain and it is predicted that a larger or smaller feed rate than the optimum one will result in excessive diameter expansion.…”
Section: Resultssupporting
confidence: 87%